My Time - Wiggins, Bradley; Fotheringham, William (London Yellow Jersey Press, 2012)
On 22 July 2012 the author made history as the first British cyclist to win the Tour de France. Ten days later at the London Olympic Games he won gold in the time trial to become his country's most decorated Olympian. In an instant 'Wiggo', the kid from Kilburn, was a national hero. This title tells the story of his remarkable journey.
Include Illustrations, Appendix and Index.
English Biography.
Keywords: Great Britain -- Cyclists -- Bicycle racing